Research on the Transient Hydraulic Characteristics of Multistage Centrifugal Pump During Start-Up Process - Yun, Long; Bin, Lin; Jie, Fang; Rongsheng, Zhu; Qiang, Fu (Frontiers in Energy Research, 2020)
Compared with the periodic unsteady flow induced by single-stage centrifugal pump, the internal flow state of multistage centrifugal pump is more complicated and the flow is more disordered. In this paper, the start-up process is divided into two stages: the closed-valve transition and the open-valve transition. The transient operation process is simulated numerically, and the pump characteristics and the evolution characteristics of the internal flow field are analyzed. It is found that multistage centrifugal pump start-up process of the closed-valve transition, when the impeller does the same work, compared with the steady state at the same speed, the mechanical energy in the internal flow field is converted into more kinetic energy and less pressure. Compared with the steady state at the same flow rate, in the initial stage of the open-valve start-up process, the stall group in the impeller flow channel is larger and the number of stall groups is more during the transient process, which exacerbates the rotational stall of the internal flow of the impeller, and the flow is more disordered. As a result, the amplitude of the hump fluctuation is greater than that under the same flow steady state. The research on the transient characteristics of the low specific speed multi-stage centrifugal pump during startup conditions is of great significance to the safety and reliability of nuclear power equipment and systems.